The third one
3(x+5) = 3 * x + 3 * 5
Answer:
See the graph attached. It has one solution: (6,-4)
Step-by-step explanation:
The slope-intercept form of a line is:
![y=mx+b](https://tex.z-dn.net/?f=y%3Dmx%2Bb)
Where m is the slope and b is the intersection of the line with the y-axis.
Given the first equation ![y =\frac{-1}{2}x -1](https://tex.z-dn.net/?f=y%20%3D%5Cfrac%7B-1%7D%7B2%7Dx%20-1)
You can identify that:
b=-1
Substitute y=0 to find the intersection with the x-axis
![0 =\frac{-1}{2}x -1\\1(-2)=x\\x=-2](https://tex.z-dn.net/?f=0%20%3D%5Cfrac%7B-1%7D%7B2%7Dx%20-1%5C%5C1%28-2%29%3Dx%5C%5Cx%3D-2)
This line passes through the points (0,-1) and (-2,0)
Given the second equation:
![-2 + y = -6](https://tex.z-dn.net/?f=-2%20%2B%20y%20%3D%20-6)
Solve for y:
![y = -6+2\\y=-4](https://tex.z-dn.net/?f=y%20%3D%20-6%2B2%5C%5Cy%3D-4)
It passes through the point (0,-4).
Now, you can graph. See the figure attached.
It has one solution,which is the point of intersection of both lines: (6,-4)
Answer:
I think its the first answer
Step-by-step explanation: